Positive Effects of a Healthy Snack (Fruit) Versus an Unhealthy Snack (Chocolate/Crisps) on Subjective Reports of Mental and Physical Health: A Preliminary Intervention Study - Smith, Andrew Paul; Rogers, Rosannagh (Frontiers in Nutrition, 2014)
Background/Aims: Recent research has shown associations between type of snack and wellbeing. These studies have been cross-sectional and the aim of the present research was to examine this topic using an intervention study. Methods: A between subjects intervention study was carried out. Volunteers (100 students, mean age = 19.00 years; 27 male, 73 female) completed online questionnaires measuring anxiety and depression; fatigue, somatic symptoms, cognitive difficulties and distress at baseline. They were then randomly assigned to one of two snacking conditions – chocolate/crisps or fruit. Volunteers consumed one snack item in the mid-afternoon each day for 10 days. At the end of the intervention the volunteers completed the questionnaires again. Results: Analyses of the baseline data confirmed that consumption of chocolate was associated with greater emotional eating and depression. Analyses of covariance, with the baseline data as covariates, were carried out on the post-intervention responses. The results showed that consumption of fruit was associated with lower anxiety, depression and emotional distress than consumption of crisps/chocolate. Similarly, scores for somatic symptoms, cognitive difficulties and fatigue were greater in the crisps/chocolate condition. Conclusions: These results extend findings from cross-sectional studies and give a clearer indication of causal effects of different types of snacks on wellbeing.